2020
DOI: 10.1111/acer.14477
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Psychiatric Disorders and Alcohol Consumption Levels in an Adult Primary Care Population

Abstract: Background: Unhealthy alcohol use frequently co-occurs with psychiatric disorders; however, little is known about the relationship between psychiatric disorders and alcohol consumption levels. Understanding varying levels of unhealthy alcohol use among individuals with a variety of psychiatric disorders in primary care would provide valuable insight for tailoring interventions. Methods: We conducted a cross-sectional study of 2,720,231 adult primary care patients screened for unhealthy alcohol use between 2014… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 50 publications
1
15
0
Order By: Relevance
“…To adjust for patients' medical comorbidities, we used the Charlson comorbidity score, which estimates the 1year mortality risk based on a weighted score of 17 medical conditions (Charlson et al, 1987;Deyo et al, 1992). We also identified whether individuals had an alcohol use disorder diagnosis, drug use disorder diagnosis, mental health condition (Palzes et al, 2020a(Palzes et al, , 2020b; depression, bipolar disorder, schizophrenia, schizoaffective disorder, anxiety disorder, panic disorder, obsessive-compulsive disorder, pervasive developmental disorder, anorexia nervosa, and bulimia nervosa), or substance abuse-related medical condition (SAMC; Weisner et al, 2001) in the year prior to index date, based on ICD-9 and ICD-10 codes. We used the NDI as a proxy for individual socioeconomic status (SES) and divided patients into quartiles based on the overall distribution (Messer et al, 2006).…”
Section: Patient and Provider Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…To adjust for patients' medical comorbidities, we used the Charlson comorbidity score, which estimates the 1year mortality risk based on a weighted score of 17 medical conditions (Charlson et al, 1987;Deyo et al, 1992). We also identified whether individuals had an alcohol use disorder diagnosis, drug use disorder diagnosis, mental health condition (Palzes et al, 2020a(Palzes et al, , 2020b; depression, bipolar disorder, schizophrenia, schizoaffective disorder, anxiety disorder, panic disorder, obsessive-compulsive disorder, pervasive developmental disorder, anorexia nervosa, and bulimia nervosa), or substance abuse-related medical condition (SAMC; Weisner et al, 2001) in the year prior to index date, based on ICD-9 and ICD-10 codes. We used the NDI as a proxy for individual socioeconomic status (SES) and divided patients into quartiles based on the overall distribution (Messer et al, 2006).…”
Section: Patient and Provider Characteristicsmentioning
confidence: 99%
“…Unhealthy alcohol use is a significant public health problem associated with many common medical and mental health conditions (Palzes et al, 2020b;Sterling et al, 2020), and is often a precursor to alcohol use disorder and related medical problems (Mertens et al, 2003). A recent large-scale combined analysis found a positive and curvilinear association between the level of alcohol consumption and all-cause mortality, with the minimum mortality risk around or below 100 g per week (Wood et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Studies shown that patients with AUD have higher prevalence of comorbid psychiatric disorders including schizophrenia, mood disorders, anxiety disorders and personality disorders [25,26]. In addition, insomnia is frequent in this population and may contribute to anxiety and depressive symptoms and cognitive impairment [27].…”
Section: Discussionmentioning
confidence: 99%
“…KPNC provides care to a population insured through employer-based plans, Medicare, Medicaid, and health insurance exchanges. KPNC has 21 medical centers, 233 medical offices, and 2,147 adult primary care physicians and providers, and provides specialty psychiatry and addiction treatment as a covered benefit ( 23 ).…”
Section: Methodsmentioning
confidence: 99%